Dark bites - Kenyon, Sherrilyn, 1965- (Kenyon, Sherrilyn, 1965- Dark-hunter novel., 2014)
The complete collection of short stories written for the Dark-Hunter series includes "Phantom Lover" and "Love Bytes" as well as a new, previously unreleased title and tales that have only been published exclusively on the author's website.